HUBUNGAN PERSEPSI TERHADAP PELAKSANAAN SENAM PAGI DENGAN KONSENTRASI BELAJAR DAN KESEHATAN MENTAL SISWA SEKOLAH DASAR - Julkariadi, Muhammad; Lukman; Tiassari Janjang Suminar (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study aimed to examine the relationship between students’ perceptions of morning exercise implementation and their learning concentration and mental health at SDN 18 Mataram. A quantitative correlational design was employed with 86 purposively selected students from grades IV, V, and VI. Data were collected using three Likert-scale questionnaires measuring perceptions of morning exercise, learning concentration, and mental health. The instruments showed acceptable internal consistency, with Cronbach’s alpha values of 0.818, 0.674, and 0.719, respectively. Descriptive results indicated mean scores of 80.12 for perceptions of morning exercise, 79.78 for learning concentration, and 82.22 for mental health. Simple linear regression analysis revealed positive associations between perceptions of morning exercise and learning concentration (b = 0.655; p < 0.001; R² = 0.376), as well as mental health (b = 0.405; p < 0.001; R² = 0.228). These findings suggest that students with more positive perceptions of morning exercise tend to report better learning concentration and mental health. Therefore, morning exercise may be maintained as a structured school routine, although further studies with stronger designs are still needed.